2008
DOI: 10.1002/elan.200704125
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites: From Fabrications to Electrochemical Bioapplications

Abstract: Nanostructured materials including nanoparticles, nanowires, nanobands and carbon nanotubes (CNT) have been intensively investigated due to their fantastic size effect and superior chemical and physical properties and functions. Nanocomposites can be fabricated not only with different nanostructured materials, but also with various biomolecules and conducting polymers to possess unique hybrid properties characteristic of neither the incorporated components nor the host matrices. The nanocomposites may be confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(88 citation statements)
references
References 202 publications
(102 reference statements)
0
86
0
1
Order By: Relevance
“…The use of carbon nanotubes has attracted a great deal of attention not only to develop better structural-reinforced materials thanks to the advantageous CNT mechanical properties (high stiffness, tensile strength) but also for conferring remarkable conductivity to polymer matrices (Ajayan et al, 2003;Wang & Musameh, 2003;Barrera et al, 2005, Harris, 2004Moniruzzaman et al, 2006;Coleman, 2006;Spitalsky et al, 2010;Li et al 2008;Xiao & Li, 2008;Martone et al, 2010). However the fabrication of high performance CNT composites still results challenging and several important requirements should be fulfilled for an effective improvement of CNTbased composite properties.…”
Section: General Considerations and Fabrication Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of carbon nanotubes has attracted a great deal of attention not only to develop better structural-reinforced materials thanks to the advantageous CNT mechanical properties (high stiffness, tensile strength) but also for conferring remarkable conductivity to polymer matrices (Ajayan et al, 2003;Wang & Musameh, 2003;Barrera et al, 2005, Harris, 2004Moniruzzaman et al, 2006;Coleman, 2006;Spitalsky et al, 2010;Li et al 2008;Xiao & Li, 2008;Martone et al, 2010). However the fabrication of high performance CNT composites still results challenging and several important requirements should be fulfilled for an effective improvement of CNTbased composite properties.…”
Section: General Considerations and Fabrication Methodsmentioning
confidence: 99%
“…2006; Céspedes et al, 1996;Xiao & Li., 2008;Li et al, 2008;Li et al, 2009;Rajesh et al, 2009;Navratil & Barek, 2009). Nanocomposite for electrode applications are formed by at least one conducting and one insulating phase.…”
Section: Advances In Composite Materials For Medicine and Nanotechnolmentioning
confidence: 99%
See 2 more Smart Citations
“…MWCNTs and GR have advantages in the biosensor field because of their unique physicochemical properties including high surface area, excellent electric conductivity, strong mechanical strength, good adsorptive ability and excellent biocompatibility [25][26][27]. Moreover, studies have revealed that nanohybrid can often combine the merits of each component and exhibit enhanced properties [28][29][30]. Previous literatures have proved that MWCNTs-GR hybrid can generate synergy effect, which can greatly accelerate electron-transfer processes and provide a promising electrochemical sensing platform [31][32][33].…”
Section: Introductionmentioning
confidence: 99%